Turning Your Presentations/Posters to Publications - Shweta Prasad; Ajay Garg; Jitender Saini (Indian Journal of Radiology and Imaging)
A scientific manuscript or paper is invariably the ultimate goal of most scientific endeavors and in a majority of cases, the final manuscript often begins as an abstract submitted to a conference to be presented as either a poster or an oral presentation. It is practically possible for authors to use a conference presentation as a basic template to expand and write a complete manuscript. However, it is imperative for authors to acknowledge the limitations of these abstracts and make attempts to improve the quality of work before embarking on writing a full-length manuscript. This article aims to provide a structured approach to how to write a paper primarily based on a conference abstract, along with examples and limitations.